Learning Analytical Epidemiology Concepts Through Research Projects During Community Medicine Clinical Postings - Hemant D Shewade; Niranjana Jayakumar; Bhuvaneswary Sunderamurthy (Medsci Publications, 2013)
Background: Innovative methods are required to teach epidemiology to medical undergraduate students. Aim: To assess the effect of research projects, as a part of community medicine clinical postings, in knowledge and skill attainment pertaining to analytical epidemiology. Methods: Forty MBBS students were involved in conducting a hospital-based matched case-control study to determine the risk factors for hypertension. Faculty of Community Medicine facilitated the process. Students critically analyzed the study by comparing the concepts (taught in briefing and from the study material) with the actual study conducted by them. Pre-test questions were repeated as post-test; in addition, open ended questions were given in the form of a written test. Results: We found that average post test score was 13.8 (max 20); an increase by 10.6 (0.95 CI: 9.3, 11.9). Of the 36 take home points (concepts), it was found that 13 of them were understood by ≥75% students, 13 by <75% (but ≥50%), and 10 by <50% students. Conclusion: Our methodology of simultaneously conducting briefing sessions and data collection, with the aim of empowering MBBS students to critically analyze the research project, has enabled them to grasp various concepts of analytical epidemiology which, usually, are not taught to them.